An experimental study into the influence of works council advice on managerial decision-making - S. Sapulete; Arjen van Witteloostuijn; W. Kaufmann (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
This paper experimentally studies the potential effect of works councils on managerial decision-making. Empirical evidence on the influence of works councils in organizations is still mixed. Therefore, this experimental study tries to gain more insights into the mechanisms that may underlie the impact of works council advice. First, we try to explain whether advice given by a works council influences the decision managers make. Second, we attempt to explain whether works councils delay the decision-making process. In order to answer these questions, we conducted experiments with undergraduate students, who played a two-player Prisoner's Dilemma price-setting game. One group received advice from a works council, whilst the other group did not. As expected, advice does have an influence on decision-making: receiving advice for setting a low price leads to a higher likelihood to set a low price as well, and receiving advice to set a high price leads to a high price decision. Female managers are more likely to take the works council advice into account. Subjects with an other-regarding orientation tend to choose a high price, even when they are advised to opt for a low price. Further, decision-making is not delayed by the advice, but there is an interaction effect with gender: female managers receiving advice tend to think longer about their decision.
Keywords: 330; works council advice; experimental economics; managerial decision-making